2017
DOI: 10.1016/j.ijom.2016.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the C-terminal telopeptide test in predicting the development of bisphosphonate-related osteonecrosis of the jaw: a systematic review

Abstract: This systematic review evaluated the efficacy of the morning fasting serum C-terminal telopeptide (CTX) test in predicting the development of bisphosphonate-related osteonecrosis of the jaw (BRONJ). A comprehensive search of studies published up to March 2016, and listed in the PubMed/MEDLINE, Web of Science, and Cochrane Library databases, was performed in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. This review has been registered in the PROSPERO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 34 publications
2
16
0
8
Order By: Relevance
“…In the hypothetical clinical cases, no C-terminal telopeptide test was used to predict the development of BP-related ONJ because a systematic review revealed that among 1,442 patients receiving alendronate and undergoing tooth extraction, 2% developed BP-related ONJ. The results showed evidence that the C-terminal telopeptide test seems to have no predictive value for determining the risk of ONJ in patients taking AM [30].…”
Section: Discussionmentioning
confidence: 94%
“…In the hypothetical clinical cases, no C-terminal telopeptide test was used to predict the development of BP-related ONJ because a systematic review revealed that among 1,442 patients receiving alendronate and undergoing tooth extraction, 2% developed BP-related ONJ. The results showed evidence that the C-terminal telopeptide test seems to have no predictive value for determining the risk of ONJ in patients taking AM [30].…”
Section: Discussionmentioning
confidence: 94%
“…Bizim hasta grubumuzda da altı hasta intravenöz olarak zolendronik asit kullanırken, sadece iki hasta oral olarak ibandronate kullanmaktadır. Konuyla ilgili günümüze kadar yapılmış çalışmalara bakıldığında bifosfanat kullanımına bağlı görülen BRONJ oranı oral kullanımlarda %0.01 ile %0.06; intranevöz kullanımlarda ise %0.8 ile %12 arasındadır (35,36,37,38). Yapılan bir çalışmaya göre ise meme kanseri nedeniyle intravenöz yolla bifosfonat kullanan hastaların %4.3ünde; multiple myeloma nedeniyle bifosfonat kullanan hastaların ise %6.9 unda spontan olarak çene kemiklerinde osteonekroz gelişmiştir (34).…”
Section: Discussionunclassified
“…Controversy and debate exist in the scientific literature regarding the recommendation of the CTX test for MRONJ risk 54 .Only three studies19,20,24 (30%) reported a positive association between CTX and MRONJ. One of the difficulties in evaluating the association of CTX with MRONJ is the presence of confounding factors, such as fasting, that can alter CTX values among individuals55,56 . A previous SR revealed no significant differences in mean CTX values between MRONJ patients and control participants54 .…”
mentioning
confidence: 99%
“…A previous SR revealed no significant differences in mean CTX values between MRONJ patients and control participants54 . Another recent SR also indicated that the CTX test has no predictive value in determining the risk of MRONJ in patients taking BPs55 .Bone formation can be evaluated by the serum levels of BAP, an osteoblast-specific enzyme, the second most investigated biomarker in the included studies. Three studies 20,28,49 showed significantly lower BAP levels in MRONJ patients taking oral BPs, while seven other studies17,18,23,26,29,31,30 lacked evidence associating BAP levels with MRONJ.…”
mentioning
confidence: 99%